BARD1 deletion in a patient with suspected hereditary colorectal cancer - Nobue Takaiso; Issei Imoto; Akiyo Yoshimura; Akira Ouchi; Koji Komori; Hiroji Iwata; Yasuhiro Shimizu (Human Genome Variation)
Abstract Deleterious germline variants in the BRCA1-associated ring domain (BARD1) gene moderately elevate breast cancer risk; however, their potential association with other neoplasms remains unclear. Here, we present the case of a 43-year-old female patient diagnosed with sigmoid colon adenocarcinoma whose maternal family members met the Amsterdam Criteria II for Lynch syndrome. Comprehensive multigene panel testing revealed a heterozygous BARD1 exon 3 deletion.